The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.9734/ajrb/2019/v4i430073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oral Intake of African Locust Bean on Fasting Blood Sugar and Lipid Profile of Albino Rats

Abstract: Background: African locust bean is a condiment believed to be for the people of low class. Its health importance has not been fully known especially to the so-called high class. Aim: This study is aimed at investigating the effect of African locust bean on fasting blood sugar and lipid profile of albino rats. Methods: African locust bean (ALB) was purchased from a local market at Orita-Challenge area of Ibadan, Nigeria. They were sun dried and milled into powder using an electronic blender. The pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 21 publications
9
21
1
Order By: Relevance
“…6). This result contradicts the findings of Airaodion et al [21] who reported a non-significant difference in the LDL-cholesterol concentration when animals were treated with African locust bean for 14 days. The combined effect of increased HDLcholesterol (good cholesterol) and decreased LDL-cholesterol (bad cholesterol) in the present study resulted in an increased HDLcholesterol/LDL-cholesterol ratio in animals treated with C. olitorius leaves when compared with the control group (Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…6). This result contradicts the findings of Airaodion et al [21] who reported a non-significant difference in the LDL-cholesterol concentration when animals were treated with African locust bean for 14 days. The combined effect of increased HDLcholesterol (good cholesterol) and decreased LDL-cholesterol (bad cholesterol) in the present study resulted in an increased HDLcholesterol/LDL-cholesterol ratio in animals treated with C. olitorius leaves when compared with the control group (Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…This suggests that C. olitorius leaves may have an extrapancreatic antihyperglycemic mechanism of action. This is in agreement with the study of Airaodion et al [21] on the effect of oral intake of African locust bean on fasting blood sugar and lipid profile of albino rats. A number of other plants and extracts have also been reported to have an antihyperglycemic and an insulinstimulatory effect.…”
Section: Discussionsupporting
confidence: 93%
“…This is suggestive that V. amygdalina leaves may have an extrapancreatic antihyperglycemic mechanism of action. This is in agreement with the study of Airaodion et al [25] on the effect of oral intake of African locust bean on fasting blood sugar and lipid profile of albino rats. Several studies has shown that a number of other plants and extracts have an antihyperglycemic and an insulin-stimulatory effect [24,31,32,33].…”
Section: Discussionsupporting
confidence: 93%
“…6). This result is in agreement the findings of Airaodion et al [25] who reported a nonsignificant difference in the LDL-cholesterol concentration when animals were treated with African locust bean for 14 days but contradicts that of Airaodion et al [24] who reported a significant decrease in the LDL-cholesterol concentration when animals were treated with methanolic extract of Corchorus olitorius leaves for 14 days.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation